Nurses in patient care in clinical sepsis framework: integrative review - Moraes, Vanessa Leopoldino de (2022)
The research aims to describe the role of professional nurses to patients with septic conditions, establish factors that contribute to the occurrence of sepsis in adult ICUs and identify signs and symptoms of patients with sepsis. This is an integrative literature review, carried out in the BDENF, LILACS, SCIELO and VHL databases. The descriptors were used: Nursing; sepsis; Intensive Care Units, including original articles, between the years 2010 to 2018. The search generally brought up protocols, research on nurses' knowledge, nursing care, clinical signs, risk factors, identification of signs and symptoms and the process of nursing. The role of nurses in the context of care involves the application of comfort measures consistent with the patient's clinical conditions, implementation of institutional protocols to guide care, monitoring of care by the entire team involved and use of the nursing process. Nurses are professionals of great relevance in the intensive environment, playing the role of preventing or considerably reducing the progression of sepsis to the most severe forms.